Increased expression of Interleukin-6 related to nephritis in chickens challenged with an Avian infectious bronchitis virus variant - Fernando,Filipe S. (2015)
A Brazilian field isolate (IBV/Brazil/PR05) of avian infectious bronchitis virus (IBV), associated with development of nephritis in chickens, was previously genotyped as IBV variant after S1 gene sequencing. The aim of this study was to evaluate the levels of IL-6 in kidneys and trachea of birds vaccinated and challenged with IBV/Brazil/PR05 strain, correlating these results with scores of microscopic lesions, specific IBV antigen detection and viral load. The up-regulation of IL-6 and the increased levels of viral load on renal and tracheal samples were significantly correlated with scores of microscopic lesions. Reduced levels of viral load were detected in kidneys of birds previously vaccinated and challenged, compared to non-vaccinated challenged group, although markedly microscopic lesions were observed for both groups. The expression of IL-6, present both in the kidney and in the tracheas, was dependent on the load of the virus present in the tissue, and the development of lesions was related with IL-6 present in the tissues. These data suggest that variant IBV/Brazil/PR05 can induce the expression of proinflammatory cytokines in a manner correlated with viral load and increased IL-6 is involved in the tissue with the influx of inflammatory cells and subsequent nephritis. This may contribute with a model to the development of immunosuppressive agents of IL-6 to prevent acute inflammatory processes against infection with IBV and perhaps other coronaviruses, as well as contribute to the understanding of the immunopathogenesis of IBV nephropatogenic strains.